A review on tensile and morphological properties of poly (lactic acid) (PLA)/ thermoplastic starch (TPS) blends. Issue 18 (12th December 2019) - Zaaba, Nor Fasihah; Ismail, Hanafi
ABSTRACT: Of late, a serious argument amongst researchers regarding the environmental issues has led to increase the concern worldwide through the development of novel biodegradable materials. Generally, polylactic acid (PLA) and thermoplastic starch (TPS) have been considered as alternative to replace non-degradable polymer materials due to their biodegradability and competitive cost. Hence, this work raises an overview with a specific focus on the tensile and morphology properties of PLA/TPS blends. Numerous chemical modifications were employed to improve the interfacial adhesion between the PLA and the starch phases. As a result, an improvement of tensile properties of the PLA/TPS blends were obtained.